The Current Account in Perspective : Lessons from the Italian Experience. (IMF Working Papers; Working Paper, 1990)
This paper draws some lessons about policies toward the current account from Italy's balance of payments history between 1960 and 1988. The key role of speculative capital flows during every major episode of external imbalance brings out the limitations of exchange rate rules that focus exclusively on the current account. Simple saving-investment rules would also have failed to avert Italy's balance of payments crises. These arose in the context of widening current deficits due to a rising investment ratio and/or a widening private imbalance, which should have been self-correcting according to the commonly proposed saving-investment rules.